PENGARUH UTANG LUAR NEGERI, INFLASI DAN NET EKSPOR TERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA - Pahimah, Nurul; Ichsan, Ichsan (Faculty of Economics and Business, Universitas Malikussaleh, 2024)
This research aims to determine the influence of foreign debt, inflation and net exports on gross domestic product (GDP) in Indonesia. This research uses secondary data from 1980-2022 obtained from the World Bank. The data analysis uses a dynamic model, namely Autoregressive Distributed Lag (ARDL) model. The research results show that in the short term, foreign debt has a positive and insignificant effect on GDP, while in the long term, foreign debt has a positive and significant effect on Indonesia's gross domestic product. Inflation, in the short and long terms, has a negative and significant effect on Indonesia's GDP. Net exports, in the short term, have a negative and significant effect on Indonesia's GDP, while in the long term, net exports have a positive and insignificant effect on Indonesia's GDP.